The Impact of Training and Mentoring on Empowering MSMEs through the Bestee Program at Bank BTPN Syariah MMS Bandar Kedungmulyo Jombang - Murningsih, Antik Wahyu Sri (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: To analyze the impact of training and mentoring on empowering MSMEs through the bestee program at the BTPN Syariah bank. Design/Methode/Approach: this research uses qualitative methods that focus on in-depth observation. Research Findings: The results of the research show that the impact of training and mentoring on empowering MSMEs is very influential on business development, thereby creating a stronger business environment and advancing local economic growth. Theoretical contribution/Originality: The impact of training and mentoring on empowering MSMEs through the Bestee program. Practitionel/Policy implications: Training and mentoring for MSMEs has a big influence on business development. Research limitation: The distance to the research location is quite far and sometimes customers are difficult to contact.